Orbital selective dynamics in Fe-pnictides triggered by polarized pump pulse excitations. (29th December 2021) - Adhikary, Ganesh; Saha, Tanusree; Rebernik Ribič, Primož; Stupar, Matija; Ressel, Barbara; Urbančič, Jurij; De Ninno, Giovanni; Thamizhavel, A.; Maiti, Kalobaran
Abstract: Quantum materials display exotic behaviours related to the interplay between temperature-driven phase transitions. Here, we study the electron dynamics in one such material, CaFe2 As2, a parent Fe-based superconductor, employing time- and angle-resolved photoemission spectroscopy. CaFe2 As2 exhibits concomitant transition to spin density wave state and tetragonal to orthorhombic structure below 170 K. The Fermi surface of this material consists of three hole pockets, β and around the Γ-point and two electron pockets around the X -point. The hole pockets have d xy, d yz and d zx orbital symmetries. The β band constituted by d xz / d yz orbitals exhibits a gap across the magnetic phase transition. We discover that polarized pump pulses can induce excitations of electrons of a selected symmetry. More specifically, while s -polarized light (polarization vector perpendicular to the xz plane) excites electrons corresponding to all the three hole bands, p -polarized light excites electrons essentially from, bands which are responsible for magnetic order. Interestingly, within the magnetically ordered phase, the excitation due to the p -polarized pump pulses occur at a time scale of 50 fs, which is significantly faster than the excitation induced by s -polarized light ( ∼ 200 fs). These results suggest that the relaxation of different ordered phases occurs at different time scales and this method can be used to achieve selective excitations to disentangle complexity in the study of quantum materials.